2011
DOI: 10.1155/2011/693253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Production, and Biotechnological Applications of Exopolysaccharides and Polyhydroxyalkanoates by Archaea

Abstract: Extreme environments, generally characterized by atypical temperatures, pH, pressure, salinity, toxicity, and radiation levels, are inhabited by various microorganisms specifically adapted to these particular conditions, called extremophiles. Among these, the microorganisms belonging to the Archaea domain are of significant biotechnological importance as their biopolymers possess unique properties that offer insights into their biology and evolution. Particular attention has been devoted to two main types of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(151 citation statements)
references
References 91 publications
(140 reference statements)
1
149
0
1
Order By: Relevance
“…Our recent study by Das et al (2014) indicated that Haloferax strain BBK2 was also resistant to cadmium (Cd) and accumulated 21.08 and/or 15.19 % of Cd in the presence of 0.5/1 mM Cd. Haloferax is known to produce exopolysaccharide (EPS) which protects the cells from direct contact with the metals and hence its resistance (Poli et al 2011). Halococcal cells resist lysis when suspended in low-osmolarity solutions (3.5 % NaCl) (Mani et al 2012;Legat et al 2013).…”
Section: Effect Of Zn and Zno Nps On Growth Of Halophilic Archaeamentioning
confidence: 99%
“…Our recent study by Das et al (2014) indicated that Haloferax strain BBK2 was also resistant to cadmium (Cd) and accumulated 21.08 and/or 15.19 % of Cd in the presence of 0.5/1 mM Cd. Haloferax is known to produce exopolysaccharide (EPS) which protects the cells from direct contact with the metals and hence its resistance (Poli et al 2011). Halococcal cells resist lysis when suspended in low-osmolarity solutions (3.5 % NaCl) (Mani et al 2012;Legat et al 2013).…”
Section: Effect Of Zn and Zno Nps On Growth Of Halophilic Archaeamentioning
confidence: 99%
“…PHAs are polyesters composed of hydroxy fatty acids, synthesized and stored as insoluble inclusions in the cytoplasm [76]. They serve as intracellular storage material of carbon source and energy.…”
Section: Polyhydroxyalkanoates: Definition Classification and Biosymentioning
confidence: 99%
“…The enzymes responsible for this reaction are PHA synthases. Therefore, it is considered that the key enzymes for PHA production are the polyester synthases [76,78,80]. In the Bacteria domain, where these kind of proteins have been studied extensively, they are divided into four classes depending on the subunit composition and their substrate [76,77,80].…”
Section: Polyhydroxyalkanoates: Definition Classification and Biosymentioning
confidence: 99%
See 1 more Smart Citation
“…Marine bacteria have recently attracted attention as potentially useful candidates for the production of PHAs.. The main advantage of biodegradable polymers is that anaerobic microbes completely degraded to water, carbon dioxide and methane in various environments such as soil, sea, lake water and sewage and so it is disposable without harm to the environment (12).Although a few kinds of marine bacteria have been investigated for PHA production under some marine conditions, characterization have not been done in details of the resultant PHAs Haloferax, Haloarcula, Natrialba, Haloterrigena, Halococcus, Haloquadratum, Halorubrum, Natronobacterium, Natronococcus and Halobacterium some Haloarchaeal species have found to be efficient producer of PHB (13).Bacterial genera like Beneckea and Vibrio have been found to be first reported potent producers of PHA isolated from marine sediments (14).…”
Section: Efficient Microbes As Bioplastic Producersmentioning
confidence: 99%